Promoting electrochemical reduction of CO2 to ethanol by B/N-doped sp3/sp2 nanocarbon electrode - Liu, Yanming; Yang, Haolei; Fan, Xinfei; Shan, Bing; Meyer, Thomas J. (Chinese chemical letters, 2022)
Electrochemical reduction of CO2 to value-added chemicals holds promise for carbon utilization and renewable electricity storage. However, selective CO2 reduction to multi-carbon fuels remains a significant challenge. Here, we report that B/N-doped sp3/sp2 hybridized nanocarbon (BNHC), consisting of ultra-small nanoparticles with a sp3 carbon core covered by a sp2 carbon shell, is an efficient electrocatalyst for electrochemical reduction of CO2 to ethanol at relatively low overpotentials. CO2 reduction occurs with a Faradaic efficiency of 58.8%-69.1% for ethanol and acetate production at −0.5 ∼ −0.6 V (vs. RHE), among which 51.6%-56.0% is for ethanol. The high selectivity for ethanol is due to the integrated effect of sp3/sp2 carbon and B/N doping. Both sp3 carbon and B/N doping contribute to enhanced ethanol production with sp2 carbon reducing the overpotential for CO2 reduction to ethanol. B/N-doped sp3/sp2 nanocarbon is efficient for electrochemical reduction of CO2 to ethanol with high selectivity at low overpotential. Both sp3 carbon and B/N doping contribute to enhanced ethanol production with sp2 carbon reducing the overpotential for CO2 reduction to ethanol. [Display omitted]